Delphi Technique: Enhancing Research in Technical and Vocational Education - Nashir, Irdayanti Mat; Mustapha, Ramlee; Yusoff, Abdullah (Journal of Technical Education and Training, 2015)
Empirical studies conducted within the Technical and Vocational Education (TVE) discipline in Malaysia tends to give greater emphasis to quantitative data collection techniques. Aware of the potential usefulness of combination of techniques, this paper discusses the application of the Delphi technique where qualitative and quantitative data collection techniques are used to reach useful results. The Delphi technique provides the opportunity for researchers to gather input from participants without requiring them to work face-to-face. Often, the process is used to find consensus among experts who have differing views and perspectives. The Delphi technique enables group problem-solving using an iterative process of problem definition, discussion, feedback, and revisions.This paper discusses the basics of the Delphi techniques, its application potential, the selection of expert panels and the means on how consensus can be reached among the participants using examples from our past research using the technique.